Features of the international manager leader of the near future - findings of the research = Cechy menedżera-przywódcy niedalekiej przyszłości - wyniki badań - Glinkowska, Beata (Zielona Góra: Faculty of Economics and Management Press)
The paper covers characteristics of the conducted research, including definitional approach to the essence of the terms: manager and leader. Particular attention was paid to the qualities of modern manager-leader and the qualities of manager-leader of the future, including globalization and internationalisation. The research part contains findings of the author`s own research which were confronted with the results of studies existing in this area in the subject literature.
Keywords: menedżer; menedżer-przywódca; organization; przedsiębiorstwo; organizacja; manager; manager-leader; enterprise